AJARAN BUDI PEKERTI DALAM SERAT SANA SUNU KARYA YASADIPURA II - Rochimansyah Rochimansyah (p-ISSN 2356-0576, 2015)
Abstract: Products of the Javanese community culture one of them is a classic text in the form of text script. Text script made by the author based on experience or condition of that society. The actual content or message from the text script that are relevant to current conditions can be used as guidance in social life. Text script of Sana Sunu There is a literary work that is presented in the form tembang macapat. Contents contained in the text script is a message advice for  child  to achieve success in life. Key words: character, text script of sana sunu   Abstrak: Produk Masyarakat budaya Jawa salahsatunya adalah naskah klasik yang berbentuk serat . Serat dibuat oleh pengarangnya berdasarkan pengalaman dan atau kondisi masyarakat itu. Kandungan isi atau pesan yang ada dalam serat yang relevan dengan kondisi saat ini dapat dijadikan sebagai pedoman dalam kehidupan bermasyarakat. Serat Sana Sunu adalah karya sastra yang disajikan dalam bentuk tembang macapat. Isi yang terkandung dalam serat tersebut merupakan pesan nasehat kepada seorang anak (remaja) untuk meraih sukses dalam hidup.   Kata kunci: budi pekerti, serat sana sunu